2015
DOI: 10.1371/journal.pone.0133125
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Aspirin Eugenol Ester on Thrombosis in κ-Carrageenan-Induced Rat Tail Thrombosis Model

Abstract: Based on the prodrug principle, aspirin eugenol ester (AEE) was synthesized, which can reduce the side effects of aspirin and eugenol. As a good candidate for new antithrombotic and anti-inflammatory medicine, it is essential to evaluate its preventive effect on thrombosis. Preventive effect of AEE was investigated in κ-carrageenan-induced rat tail thrombosis model. AEE suspension liquids were prepared in 0.5% sodium carboxymethyl cellulose (CMC-Na). AEE was administrated at the dosage of 18, 36 and 72 mg/kg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…The positive effects of AEE on the symptoms of inflammation, fever, pain and thrombosis had been confirmed in animal disease model [9, 11, 13]. The blood chemistry results in 15-day oral dose toxicity study showed AEE could significantly reduce the values of TG and TCH both in male and female rat, which indicated that this compound was potential for curing hyperlipidemia [11].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The positive effects of AEE on the symptoms of inflammation, fever, pain and thrombosis had been confirmed in animal disease model [9, 11, 13]. The blood chemistry results in 15-day oral dose toxicity study showed AEE could significantly reduce the values of TG and TCH both in male and female rat, which indicated that this compound was potential for curing hyperlipidemia [11].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the effects of AEE had been evaluated in animal model. The results showed that AEE had positive effects on antithrombosis, anti-inflammatory, analgesia and antipyretic [9, 11, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Aspirin, known as acetylsalicylic acid (ASA), is commonly used as a classic non-steroidal anti-inflammatory drug (NSAID) to relieve minor aches and treat inflammation and cardiovascular diseases [3,4]. However, this type of pharmaceutical has been detected in the aquatic environment at trace concentrations (ng to µg/L), which can prolong exposure to environmentally relevant concentration and considerably increase the toxicity considerably, resulting in negative consequences for aquatic life and human beings [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…ASA has an inhibitory effect on platelets in blood. This antiplatelet effect prevents the formation of blood clots in blood vessels, especially in people with atherosclerosis (blood vessels stenosis) [7,8]. The increased use of ASA causes increased ASA concentration in wastewater as well as in surface and underground water and thus affects aquatic ecosystems [9].…”
Section: Introductionmentioning
confidence: 99%